1867 N.H. Gen. Stat. 206, ch. 98, §§ 1-4 - (:unkn) unknown (General Publisher, 1854)
Provided the board of firewards the ability to regulate the import/export of Gunpowder. Also prohibited the storage of gunpowder in quantities exceeding 25 pounds
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER